Influence of systemic vitamin D administration and local photobiomodulation on bone repair: Histomorphometric, histochemical, and immunohistochemical study in rat calvaria - dos Santos Santinoni, Carolina; Novaes, Wesley Fonseca; Caldeira, Marcela Lucio; Mori, Graziela Garrido; Benatti, Liliane Aparecida Tanus; Badaró, Maurício Malheiros; de Andrade, Juliana Ribeiro; Duque, Thaís Mageste; Magrin, Gabriel Leonardo; Benfatti, César Augusto Magalhães; de Souza Batista, Victor Eduardo; Ervolino, Edilson [UNESP] (My University, 2025)
Objective: The purpose of the present study was to evaluate the influence of systemic vitamin D (Vit D) administration with or without local photobiomodulation (PBM) on bone repair of surgically created critical-size defects (CSD) in rat calvaria. Material and method: Thirty-two rats were used. A 5 mm DTC was created on the calvaria of each animal. The animals were randomly distributed into four experimental groups (n = 8): Control: no treatment; Vit D: systemic Vit D administration through gavage; PBM: local irradiation with low-intensity laser therapy; Vit D/PBM: systemic Vit D administration through gavage and local irradiation with low-intensity laser therapy. The animals were euthanized 15 days after treatments. It was evaluated newly formed bone area (NFBA), percentage of mature and immature collagen fibers (picrosirius red staining and polarized light), immunohistochemical identification of tartrate-resistant acid phosphatase (TRAP), transforming growth factor (TGF), and osteocalcin (OCN). Data were statistically analyzed (ANOVA, Kruskal-Wallis, p < 0.05). Results: All experimental groups presented similar statistical results in the evaluated parameters. Some qualitative differences were observed, as follows. Groups PBM, Vit D, and Vit D/ PBM presented a slight amount of newly formed bone. Group Vit D presented a higher amount of mature collagen fibers. Groups Vit D and PBM presented higher immunoexpression of OCN than other experimental groups. Conclusion: It can be concluded that Vit D and PBM did not significantly increase the amount of bone tissue formed but showed a trend towards enhanced bone maturation in the early healing stages of critical-sized defects surgically created in rat calvaria.
Keywords: Bone regeneration; Laser therapy; Rats; Vitamin D